2014
DOI: 10.1016/j.ijsu.2014.06.008
|View full text |Cite
|
Sign up to set email alerts
|

External pancreatic duct stent reduces pancreatic fistula: A meta-analysis and systematic review

Abstract: This analysis has shown that external pancreatic duct stenting is indeed efficacious in the incidence of both any grade as well as clinically significant POPF formation following PD. Length of hospital stay was also found to be significantly less by external duct stenting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 21 publications
0
34
0
Order By: Relevance
“…Seven reviews reported a significant decrease in the POPF rate in externally stented patients, [3842,45,47] 4 reviews reported a significant decrease in the rates of Grades B and C POPFs, [38,41,42,45] and 6 reviews also reported a significant decrease in the overall morbidity rate. [3842,47] Unlike our results, the reviews did not report any differences in the overall mortality rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven reviews reported a significant decrease in the POPF rate in externally stented patients, [3842,45,47] 4 reviews reported a significant decrease in the rates of Grades B and C POPFs, [38,41,42,45] and 6 reviews also reported a significant decrease in the overall morbidity rate. [3842,47] Unlike our results, the reviews did not report any differences in the overall mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…[3842,47] Unlike our results, the reviews did not report any differences in the overall mortality rate. [3842,45,47] …”
Section: Discussionmentioning
confidence: 99%
“…Influenced by the reports in which pancreatic duct stent for pancreaticojejunostomy in PD prevents POPF (8,9), pancreatic duct stent is routinely used in many Institutions. In six recent meta-analyses, three reports demonstrated that a pancreatic duct stent was useful for preventing POPF (21)(22)(23) (Table V). On the other hand, the other three meta-analyses demonstrated that such stenting did not reduce POPF (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…There are some reports comparing the efficacy of external and internal stents, finding them to have equivalent outcome (10,17). Recent meta-analyses on stenting versus non-stenting are contradictory (18)(19)(20)(21)(22)(23). Therefore, it is still controversial whether a pancreatic duct stent should be used for pancreaticojejunal anastomosis in PD.…”
mentioning
confidence: 99%
“…(82) However, the use of an external stent was associated with reduced overall and clinically significant pancreatic fistula rates after pancreaticoduodenectomies. (83) An interesting approach after a CP was recently suggested by Di Benedetto and co-workers -duct-toduct anastomosis of the Wirsung for both pancreatic remnants. (20) An internal lost stent into the duodenum was also used to protect the anastomosis.…”
Section: Indications and Contraindications For A Central Pancreatectomentioning
confidence: 99%